한국어 문장 읽기에서 음운 정보와 철자 정보의 미리보기 효과: 안구운동 추적연구 - 백현아; 김병진; 이상민; 최원일 (언어, 2021)
This paper investigates the parafoveal preview benefits of orthographic and phonological information during Korean sentence reading as well as the effects of reading skills on parafoveal information processing. In a sentence reading task using the gaze-contingent boundary paradigm, participants were presented with parafoveal preview stimuli that were either (a) identical to the target words, (b) orthographically similar but phonologically different from the target words, (c) orthographically similar and phonologically identical to the target words, or (d) unrelated nonwords. Identical or related preview words yielded significantly shorter target fixation duration measures compared to unrelated nonwords demonstrating an orthographic preview benefit, but there was no indication of a phonological preview benefit. Participants’ reading skills affected their overall sentence reading performance and modulated the facilitative effect of identical preview words on the measures of target fixation durations. Implications of these results are discussed in relation to the models of eye movement control during reading.
Keywords: Parafoveal processing; orthographic preview benefit; phonological preview benefit; eye-tracking; Korean sentence reading